Mental and Somatic Symptoms Associated with Emotional Burnout: A Systematic Review of Research - E.B. Karpova; A.S. Stupnikov; K.M. Samerkhanova; J.A. Mashkautsan (Клиническая и специальная психология)
This article analyzes the scientific literature devoted to the study of the relationship of emotional burnout with symptoms of cardiovascular diseases, gastrointestinal diseases, immune system disorders, depression, and cognitive impairments. Methods: review and analytical method. Articles published in Russian and English in the period up to December 2023 in eLibrary, CyberLeninka, GoogleScholar, PubMed, ScienceDirect, Medline, ResearchGate were analyzed. Results: the analysis showed a link between emotional burnout and symptoms of cardiovascular diseases, gastrointestinal diseases and disorders of the immune system. Emotional burnout can also be associated with depression, asthenia, and cognitive impairment. Conclusion: mental and somatic symptoms associated with emotional burnout are highlighted.